Adaptability and stability of irrigated wheat genotypes in the Cerrado of Central Brazil - Albrecht, Julio Cesar; Vieira, Eduardo Alano; Silva, Marcio Só e; Andrade, José Maria Vilela de; Scheeren, Pedro Luiz; Trindade, Maria da Glória; Sobrinho, Joaquim Soares; Sousa, Cantidio Nicolau Alves de; Júnior, Walter Quadros Ribeiro; Junior, Walter Quadros Ribeiro; et al. (Pesquisa Agropecuaria Brasileira, 2007)
The aim of this work was to estimate the adaptability and stability of irrigated wheat genotypes under conditions of Central Brazil savannah area. Grain yield of five cultivars and nine lines of irrigated wheat was measured in assays of cultivation value and use. The assays were conducted during the years 2005 and 2006, in six locations in Minas Gerais State, three in Goiás State and one in Federal District. The data of grain yield were submitted to individual and joint ANOVA, in order to estimate the adaptability and stability parameters. Significant differences were detected between genotypes in 14 of the 16 locations evaluated. None of the evaluated genotypes have presented the behavior predicted by the method of Cruz and collaborators. Cultivar BRS 264 and the CPAC 02167 lineage were superior in all the tested conditions in the Central Brazil savannah (general adaptability). Among the other evaluated genotypes, it can be highlighted the responsiveness of the cultivars BRS 207 and EMBRAPA 22 to the improvement of environmental conditions, and the specific fitness of BRS 254 and EMBRAPA 42 cultivars to environments unfavorable to irrigated wheat.